Letter (copy) - Citrine, Walter, 1887-1983
011-0114-001 Sit. Espagne 133 WMC/WJB/AC/577 International 19th March, 1937. Mr. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VII Dear Comrade Schevenels, SAILINGS OF S.S. "YORKBROOK". I thank you for your letter of 18th instant, with reference to the ship "Yorkbrook" from Finland and note your observations relative to its cargo and destination. I note that the ship is now in the hands of the Spanish Government, so that it wouId appear to me that the best and most reliable way to get the information required would be to have the Log examined, and all that is attached to it. However, I will make enquiries of the Unions which I think would be likely to help us get to the bottom of the matter. Yours faithfully, General Secretary. 292/946/11/114